Efeito da obesidade e do teste incremental máximo na modulação autonômica cardíaca e pressão arterial ambulatorial em adultos jovens - Tricot, Gabriel Kolesny (2019)
The objective of the present study was to investigate whether obesity, a maximal incremental test and aerobic fitness influence on cardiac autonomic modulation and 24 hour blood pressure in untrained youngsters. Fifty-one healthy, untrained, 18- to 30-year-olds were evaluated: 32 eutrophic (BMI between 18.5 kg / m2 and ≤ 24.9 kg / m2), 20 males and 12 females, and 19 men with obesity (BMI between 30 kg / m 2 and ≤ 39.9 kg / m 2) divided into two experimental protocols (A: men and B: women), distinct only by the time of day the procedures were performed: B afternoon. The participants were submitted to two days of evaluations: control day and experimental day. The control day was used to monitor the R-R intervals and the blood pressure during 24 hours during the daily activities of the participants, using Holter and MAPA equipment - Ambulatory Blood Pressure Mapping. On the experimental day, prior to the repetition of the procedures of the control day, a maximal incremental test in cycle ergometer was performed, for the identification of heart rate variability threshold - HRVT and VO2peak. From the data analyzed, we observed that: Experimental protocol A: the ambulatory HRV of young people with obesity and low aerobic fitness is preserved, however, diastolic blood pressure is elevated during sleep. The incremental test caused HR elevation and hypotension in 24 h, with reduction of parasympathetic activity only in 1 h, regardless of BMI. Obesity indicators correlated with HR during sleep and ambulatory blood pressure. As well as, outpatient HR correlated with aerobic fitness. Experimental protocol B: the maximal incremental test performed in the evening period caused changes in the circadian rhythm due to increased cardiac work during sleep, but did not promote hypotension in young women. Cardiac autonomic alterations were related to aerobic fitness.